Total Quality Management in Improving Health Services - Aslinda Aslinda; Muhammad Luthfi Siraj (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This research aims to determine the implementation of Total Quality Management as an effective model for realizing quality health services at Ananda Hospital Makassar. This research method is of various types qualitative with a policy approach. The data source uses primary data via instrument observations and interviews as well as secondary data through reviewing various documents. The data analysis technique uses an interactive model, namely data collection, data condensation, data presentation, and verification/conclusion. The results of this research show that the implementation of the TQM model at Ananda Makassar Hospital was not implemented optimally due to the leadership aspect of manager Hospitals are less able to organize and organize all existing resources within the hospital and the inability of the head of the hospital to collaborate and communicate well with all Ananda Hospital staff to work together. set standard work procedures that are efficient and effective and the TQM implementation factors at Ananda Hospital can run well if the hospital can optimize the implementation of communication and collaboration factors where it is hoped that the Ananda Makassar Hospital will improve the quality of service by involving patient health organizations in provide education to patients as well as collaboration in exchanging necessary medical personnel resources done Ananda Makassar Hospital to develop the competency and work skills of doctors, nurses and staff administration hospitals in collaboration with other agencies and institutions that can provide training activities.